Família Celastraceae: caracterização química de óleos essenciais de nove espécies, compilado dos triterpenos pentacíclicos com foco nos dados de RMN de 13C, estudo fitoquímico das folhas de Pristimera celastroides e das folhas e raízes de Fraunhofera multiflora - Karen Caroline Camargo (2022)
lants belonging to the Celastraceae family are considered as promising sources of bioactive compounds, especially pentacyclic triterpenes (TPs). This work aimed to carry out a bibliographic survey of pentacyclic triterpenes isolated from Celastraceae plants between the years 2001 and 2021, a phytochemical study of the leaves of Pristimera celastroides and leaves and roots of Fraunhofera multiflora and to obtain and chemically characterize essential oils from different parts and species of this family. The results obtained were presented in three chapters. In Chapter 1, the bibliographic survey was described, and 504 pentacyclic triterpenes isolated from Celastraceae species were reported between 2001 and 2021. These were classified as friedelanes (103), quinonamethides (22), aromatics (29), dimers (50), lupanes (89), oleananes (102), ursanes (88) and others (21). In chapter 2, the results of phytochemical studies of the species P. celastroides (leaves) and F. multiflora (leaves and roots) were discussed. From the species P. celastroides, a mixture of hydrocarbons (PC-1) and carboxylic acids (PC-3 and PC-6), two esterified compounds belonging to the class of cycloarthanes [3β-acyloxy-9,19-cyclolanostan-24-ene (PC-4) and 3β-acyloxy-9,19-cyclolanostan-24,21-diol (PC-10)], β-sitosterol in its esterified form (3β-acyloxy-sitosterol, PC-8) and free form (PC-9), squalene (PC-2), gutta-percha polymer (PC-5) and vitamin E (α-tocopherol, PC-7). The phytochemical study of F. multiflora resulted in the isolation of three mixtures of hydrocarbons (FM-1a, FM-1b and FM-1c) and two mixtures composed of isomers of the class of ursanes and oleananes: olean-12-en-3,11α-diol (FM-8) + ursan-12-en-3β,11α-diol (FM-9) e ursan-11,12(13)-dien-3β-ol (FM-15) + olean-11,12(13)-dien-3β-ol (FM-16). TPs of the following types were isolated: friedelanes (friedelin, FM-2, and friedelinol, FM-14), ursanes (α-amyrin, FM-4, and ursolic acid, FM-7), oleananes (olean-11,13(18)-dien-3β-ol, FM-6) and quinonamethides (pristimerin, FM-13). In addition to these, the polymer gutta-percha (FM-3), two steroids (β sitosterol, FM-5, and 3-O-β-D-(6-O-acyloxy-glycosyl)-β-sitosterol, FM-11) and mixtures composed of macrocyclic alkaloids derived from spermidine (FM-12a, FM-12b and FM-12c) were isolated. Finally, in chapter 3, a comparative study of the chemical composition of essential oils extracted from species of Celastraceae was described. Seventeen essential oils were obtained from different parts of nine species of Celastraceae. A total of 130 different constituents were identified by GC-EM, among which the cis and trans-oxide isomers of linalool, nerylacetone, linalool, β-ionone, α-ionone, nerolidol, decanal and dodecanoic acid, detected in most essential oils. The principal component analysis showed a similarity profile in the chemical composition of the essential oils of the studied plant species. The antimicrobial and anticholinesterase activities were evaluated, in which the essential oils showed low or no inhibition. The data reported in the three chapters highlight the abundance and structural diversity of TPs isolated from Celastraceae species, as well as the results obtained in the study of essential oils can be used as a reference for carrying out chemotaxonomic studies.